The Effect of Income with Household Consumption on The Welfare of Dodol Potato Businesses Assessed From Islamic Economic Concept - Cendra, Cendra; Fauzi, Muhammad; Arzam, Arzam; Novia, Aidil; Hulwati, Hulwati; Bustami, Yuserizal; Syarif, Dafiar; Mursal, Mursal (Universitas Trunojoyo Madura, 2020)
The purposed of this study was to analyze the influence between income and household consumption on the welfare of potatoes taffy business in Lubuk Nagodang Village, Siulak Subdistrict, Kerinci regency. This study was assessing the welfare of taffy business in Islamic economic concepts and indicators. Field research with quantitative-qualitative (Mixed Method) as the method and approach used in this research. The research data was sourced from primary data, using multiple linear regression equations as a data analysis tool. This study was shown that the income partially has a significant effect on the welfare of potatoes taffy business that assessed from the Islamic economic concept. Then, household consumption partially has a significant effect on the welfare of potatoes taffy business assessed from the concept of Islamic economics. Besides, the income with household consumption simultaneously has a significant effect on the welfare of potatoes taffy business assessed from the concept of Islamic economics with a significance value of 0.000 0.05, and both variables contribute 69.2% together, while the remaining 30 ,8% influenced or explained by other factors not discussed in this study.